The Association between Religious Belief and Drug Adherence Mediated by Religious Coping in Patients with Mental Disorders - Mohadeseh Movahedizadeh; Mohammad Reza Sheikhi; Saeed Shahsavari; Hui Chen (Wolters Kluwer Medknow Publications, 2019)
Introduction: Adherence to drug regimen is an important factor in the treatment of patients with mental disorders. In some studies, religious beliefs have been shown to be effective for treatment adherence. This study aimed to investigate the association between religious beliefs and adherence to the medication regimen mediated by religious coping in patients with mental disorders. Methods: In this cross-sectional study, 164 patients with mental disorders were selected through convenient sampling from educational centers in Qazvin city. Data were collected using a demographic questionnaire, March Drug Adherence Questionnaire, Santaklara's Religious Faithfulness questionnaire, and Pargament Religious Coping questionnaire. Data were expressed as mean ± standard deviation and analyzed using descriptive and inferential statistics. Results: The mean age of the patients was 38.87 ± 14.42 years. The mean duration of the disease was 5.71 ± 5.78 years. The mean of the religious belief score was 30.90 ± 5.96, the mean of the negative religious coping score was 2.17 ± 2.94, and the mean of positive religious coping score was 6.83 ± 4.69. There was a significant positive correlation between religious beliefs, adherence to medication regimen, and positive religious coping. There was a significant negative correlation between religious beliefs, adherence to medication regimen, and negative religious coping. Conclusion: There was a significant positive correlation between religious beliefs and adherence to medication regimen in patients with mental disorders. Religious beliefs were directly associated with positive religious coping, and adherence to medication regimen was indirectly associated with negative religious confrontation.